2017
DOI: 10.1007/s12273-017-0354-3
|View full text |Cite
|
Sign up to set email alerts
|

Low-Reynolds number mixing ventilation flows: Impact of physical and numerical diffusion on flow and dispersion

Abstract: Quality assurance in computational fluid dynamics (CFD) is essential for an accurate and reliable assessment of complex indoor airflow. Two important aspects are the limitation of numerical diffusion and the appropriate choice of inlet conditions to ensure the correct amount of physical diffusion. This paper presents an assessment of the impact of both numerical and physical diffusion on the predicted flow patterns and contaminant distribution in steady Reynolds-averaged NavierStokes (RANS) CFD simulations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Only 5% of the submissions were based on first‐order discretization schemes. The use of second‐ or higher‐order discretization schemes has been recommended by—among others—Casey and Wintergerste, Chen and Srebric, Nielsen, Nielsen et al, and van Hooff and Blocken . The participants used both coupled and segregated solvers.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only 5% of the submissions were based on first‐order discretization schemes. The use of second‐ or higher‐order discretization schemes has been recommended by—among others—Casey and Wintergerste, Chen and Srebric, Nielsen, Nielsen et al, and van Hooff and Blocken . The participants used both coupled and segregated solvers.…”
Section: Methodsmentioning
confidence: 99%
“…The use of secondor higher-order discretization schemes has been recommended by-among others-Casey and Wintergerste, 18 Chen and Srebric, 19 Nielsen, 21 Nielsen et al, 22 and van Hooff and Blocken. 34 The participants used both coupled and segregated solvers. In the segregated solvers, algorithms such as SIMPLE, SIMPLEC, SIMPLEST, and the PISO scheme were used for pressure-velocity coupling.…”
Section: Submissionsmentioning
confidence: 99%
“…Numerous examples of previous studies on indoor airflows using CFD can be found in literature. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] The largest disadvantage of CFD is the need for solution verification and validation [26][27][28][29][30][31] and the large sensitivity of results to the large amount of choices a user needs to make when performing CFD simulations. 32,33 In this paper, unsteady Reynolds-averaged Navier-Stokes (URANS) CFD simulations using the renormalization group (RNG) k-e turbulence model and a large-eddy simulation (LES) using the dynamic Smagorinksy subgrid-scale model were performed for a mixing ventilation case with time-periodic supply velocities, and the results were compared in terms of dimensionless time-averaged velocities and contaminant levels inside the enclosure.…”
Section: Introductionmentioning
confidence: 99%
“…9 Finally, a recent review paper 10 on advanced air distribution methods devoted one section to IAJSs, which stated that stagnation zones and draught issues could be reduced by time-periodic supply flows. Although all aforementioned publications indicated the possible positive effects of time-periodic (or intermittent) ventilation with respect to mixing, ventilation efficiency and thermal comfort, the vast majority of research papers on mixing ventilation flows focused on constant supply velocities 1122 and a systematic study on the potential of time-periodic supply velocities for different mixing ventilation cases is currently lacking.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation